Linkages between Formal Institutions, ICT Adoption and Inclusive Human Development in Sub Saharan Africa - Antonio Rodríguez-Andrés; Voxi Amavilah; Simplice Asongu (African Governance and Development Institute (AGDI), 2016)
Using data for 49 African countries over the years spanning 2000-2012, and controlling for a wide range of factors, this study empirically assesses the effects of formal institutions on ICT adoption in developing countries. It deploys 2SLS and FE regression models, (a) to estimate what determines ICT adoption and (b) to trace how ICT adoption affects inclusive development. The results show that formal institutions affect ICT adoption in this group of countries, with government effectiveness having the largest positive effect and regulations the largest negative effect. Generally, formal institutions appear more important to ICT adoption in low income countries than middle income countries, whereas population and economic growth tend to constrain ICT adoption with low income countries more negatively affected than middle income countries. The results further demonstrate that ICT adoption affects development strongly, and that such effects are comparable to those of domestic credit and foreign direct investment. Ceteris paribus, external factors like foreign aid are more limiting to inclusive development than internal factors. This suggests that developing countries can enhance their ICT adoption for development by improving formal institutions and by strengthening domestic determinants of ICT adoption. Both represent opportunities for further research.
Keywords: G20; I10; I32; O40; O55; 330; Formal institutions; ICT adoption; panel data models; cross-country analysis